2011
DOI: 10.1097/ta.0b013e3181cc8553
|View full text |Cite
|
Sign up to set email alerts
|

Composite Grafting for Traumatic Fingertip Amputation in Adults: Technique Reinforcement and Experience in 31 Digits

Abstract: This easily performed and one-stage surgical procedure provided a reliable method for treating microsurgically nonreplantable fingertip amputations caused by hand trauma. The high overall success rate, satisfactory esthetic outcome, and good functional preservation helped patients return quickly to their daily life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
42
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 33 publications
0
42
0
1
Order By: Relevance
“…Mean static 2-PD after skin grafting was 6.5 mm. 14% of our studies (n=6) reported dynamic 2-PD, 26,4143,55,56 with an overall mean of 7.0 mm; normal range is between 2.8–4.6 mm. 67,68 All six studies were in the local flaps group (e.g.…”
Section: Resultsmentioning
confidence: 70%
See 3 more Smart Citations
“…Mean static 2-PD after skin grafting was 6.5 mm. 14% of our studies (n=6) reported dynamic 2-PD, 26,4143,55,56 with an overall mean of 7.0 mm; normal range is between 2.8–4.6 mm. 67,68 All six studies were in the local flaps group (e.g.…”
Section: Resultsmentioning
confidence: 70%
“…26,30,31,35,37,54,56 16% of our studies (n=7) evaluated cosmetic satisfaction. 17,21,27,39,43,45,55 85% of patients (112/131) reported “satisfactory” ratings and 98% of patients (105/107) reported “good” or “excellent” ratings, irrespective of treatment. 9% of our studies (n=4) evaluated other PRO measures, such as the Disabilities of the Arm, Shoulder, and Hand (DASH) score.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The treatment of digital terminal wound becomes more complicated if the soft tissue defect coexists with phalangeal fracture and tendon tear. 1 Multiple options are available for repairing such defects, including the conservative treatment with the amputation and healing by secondary intention, replantation of fingertip, and fingertip reconstruction using flap transfer.…”
mentioning
confidence: 99%